Wife as a Perpetrator of Domestic Violence Viewed from the Perspective of Criminal Law - Nining Yurista Prawitasari; Adhining Prabawati Rahmahani (Journal of Law, Politic and Humanities, 2025)
Domestic violence is a cruelty perpetrated by one partner against the other, not only leading to physical torture but also mental suffering. Victims of domestic violence are mostly women, but in reality, it is not only women who become victims of domestic violence; on the contrary, women themselves can also be perpetrators of domestic violence against their partners. An example of a case that occurred is a wife cutting off her husband's genitals. This phenomenon must receive protection from both society and the state to avoid and be free from violence and torture that have degraded the dignity and worth of humanity. The research method used is normative juridical, with the approach taken being a statutory approach.